An exploratory study on gender responsiveness of selected media outlets to the LGBTQIA+ journalists and production staff - Mabugay, Vhon Duane Ballecer 2001
Queer employees experienced gender inequality in terms of wage, remarks and job qualifications all over the world (David. 2015: Levine & Leonard. 1984). Since the media plays a vital role in society, the working conditions of queer media workers are important to assess whether gender inequality persists in their news media organizations. Through the Gendered Organization Theory by Acker (2012), the researcher aimed to find out how queer media workers experience gender inequality inside the news media organizations in the Philippines. The researcher conducted in-depth interviews patterned from the "interacting processes" concepts of the theory with researchers, writers, reporters, a content producer, section editors, and a producer from prominent newsrooms in the Philippines namely Rappler, Philippine Star and ABS-CBN News. The significant findings of this study found out that queer media did not experience gender inequality in terms of salary, promotion, beat/production designations, dress code limitations and use of makeup. However, the study proved that queer people are still victims of gender inequality due to negative remarks. Regardless if their organizations are gender-responsive, if the society remains discriminative towards queers, gender inequality will continue to persist. Hence, the implementation of gender-responsive policies were seen as urgent by the queer media worker.